Analysis of the behavior of a high earth-core rockfill dam considering particle breakage. (May 2023) - Liu, Sihong; He, Wen; Sun, Yi; Shen, Chaomin; Wang, Liujiang
Abstract: This paper presents a finite element analysis for the behavior of the Lianghekou high earth-core rockfill dam, which was just completed in construction in China. An elastoplastic constitutive model that can account for the degradation of rockfills due to particle breakage (hhu-SH-breakage model) was applied to simulate the mechanical behavior of the rockfills. The earth-core wall was analyzed by using the modified Cam-clay model combined with the Biot's consolidation theory. Numerical results are in good agreement with in-situ measurements during construction, indicating the reasonability of the numerical analysis. Based on the breakage-packing concept, which is able to extract the breakage-induced deformation from the total deformation, numerical analysis showed that the breakage-induced settlement for the extra high rockfill dam is not negligible. Inspired by the sensitivity analysis using the hhu-SH-breakage model, engineering advices were proposed to reduce the settlement of high rockfill dams.